Bulk binary ZrO2-based oxides as highly active alternative-type catalysts for non-oxidative isobutane dehydrogenation. Issue 52 (9th June 2016) - Otroshchenko, Tatyana; Radnik, Jörg; Schneider, Matthias; Rodemerck, Uwe; Linke, David; Kondratenko, Evgenii V.
Abstract : Bulk binary ZrO2 -based oxides efficiently catalyse non-oxidative dehydrogenation of isobutane to isobutylene. Abstract : Bulk binary ZrO2 -based oxides efficiently catalyse non-oxidative dehydrogenation of isobutane to isobutylene. Their activity strongly depends on the kind of second metal oxide. So designed CrZrO x showed superior activity to industrially relevant catalysts with supported Pt or CrO x species. It was also stable under alternating dehydrogenation and oxidative regeneration cycles over ca. 110 h under different reaction conditions between 550 and 600 °C.